2012
DOI: 10.3892/ijmm.2012.986
|View full text |Cite
|
Sign up to set email alerts
|

Expression of muscle-specific integrins in masseter muscle fibers during malocclusion disease

Abstract: Abstract.Integrins are heterodimeric cell surface membrane proteins linking the extracellular matrix to actin. α7B integrin is detected in proliferating and adult myofibers, whereas α7A plays a role in regenerating muscle fibers with a minor function in mature muscle fibers. The expression levels of β1A appear to be very low, whereas β1D appears to be the predominant integrin form in mature muscle. Considering the important features of masseter muscle we have studied integrin expression in masseter muscle spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 57 publications
3
40
0
Order By: Relevance
“…As previously described, Cutroneo et al. () showed that patients with UPS had an imbalance of integrin expression in the masseter muscle between the both sides, with the side affected by UPS exhibiting a lower expression of different integrin isoforms, in accordance with electromyographic studies (Piancino et al., , ) (Figure ).…”
Section: The Human Masseter Musclesupporting
confidence: 77%
See 2 more Smart Citations
“…As previously described, Cutroneo et al. () showed that patients with UPS had an imbalance of integrin expression in the masseter muscle between the both sides, with the side affected by UPS exhibiting a lower expression of different integrin isoforms, in accordance with electromyographic studies (Piancino et al., , ) (Figure ).…”
Section: The Human Masseter Musclesupporting
confidence: 77%
“…Control side , not affected by UPS showed an increasing of α7A and β1A‐integrin compared to α7B and β1D isoform. Crossbite side, expression of all of the integrin isoforms appears to be decreased compared to the integrins of the control side not affected by crossbite (from Cutroneo et al., )…”
Section: The Human Masseter Musclementioning
confidence: 98%
See 1 more Smart Citation
“…It has also been shown that MPO, during periodontal disease, mediates the immune response at the endothelial level through specific heat shock proteins which has been shown to be useful for stimulating the production of cross-reactive T cells [47][48][49][50][51][52]. In this regard, this process which sees MPO as a key modulator [53][54][55][56][57][58], has also been shown to influence the host defense mechanism that determines a subsequent activation of endothelial cell production [55,[58][59][60][61][62][63] which leads to an increased risk of future tissue damage effects due to periodontal pathogens bacteria in several oral diseases [43,[64][65][66][67][68]. Moreover, the oral microbiota is a key factor in the protection against the colonization of extrinsic pathogens that could impact systemic health [68].…”
Section: Discussionmentioning
confidence: 99%
“…The findings by Jung et al (2017) outlined in their review concur with several cases of evidence on this topic that support a wide array of oral manifestation (Del Rosso & Maddali-Bongi, 2014;Matarese et al, 2016) clearly associated with a significant impairment during SSc. These include dental (decayed, filled and missing teeth), periodontal and orofacial (microstomia, xerostomia and alveolar bone resorption) abnormalities (Amin et al, 2011;Cutroneo et al, 2012;Matarese et al, 2015).…”
Section: Dear Editormentioning
confidence: 99%